FASCISM, NEO-FASCISM, OR POST-FASCISM? CHILE, 1945-1988 - Sandra McGee Deutsch (Diálogos - Revista do Departamento de História e do Programa de Pós-Graduação em História, 2009)
The article sets out to analyze fascist and neo-fascist movements in Chile, in the period following World War II. Chile is an exemplary case for this type of analysis, as it had a significant fascist movement in the period between world wars, with several radical right organizations appearing later on. The objective of the study is to understand how the defeat of the Axis and post-war context affected these fascist movements, including some composed by women.